2013
DOI: 10.1186/1471-2334-13-458
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes after nucleos(t)ide analogues discontinuation in chronic hepatitis B patients with HBeAg-negative

Abstract: BackgroundHepatitis B e Antigen (HBeAg)-negative chronic hepatitis B (CHB) patients have an active liver disease with a high risk of progression to decompensated cirrhosis and hepatocellular carcinoma. The management strategy for HBeAg-negative CHB patients treated with nucleos(t)ide analogues (NUCs) is a topic of concern. To observe the outcomes for this population after NUCs withdrawal, HBeAg-negative CHB patients with loss of hepatitis B surface antigen (HBsAg) or sustained undetectable HBV DNA levels who h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(51 citation statements)
references
References 13 publications
1
49
1
Order By: Relevance
“…The literature search initially identified 972 papers; of those, 25 fulfilled the inclusion and exclusion criteria for this review (http://onlinelibrary.wiley.com/doi/10.1002/hep.28438/suppinfo). The main characteristics of the included studies and patients are presented in Tables and .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The literature search initially identified 972 papers; of those, 25 fulfilled the inclusion and exclusion criteria for this review (http://onlinelibrary.wiley.com/doi/10.1002/hep.28438/suppinfo). The main characteristics of the included studies and patients are presented in Tables and .…”
Section: Methodsmentioning
confidence: 99%
“…In total, 2332 (each study contribution from 11 to 401) patients were included in the 25 studies. All but one were cohort studies (three prospective, one retrospective‐prospective, and 20 retrospective, while one was a randomized study comparing the effects of 12 versus 24 months of additional therapy after response to lamivudine in HBeAg‐negative CHB . One study was found to have high quality, 14 to have acceptable quality, and 10 to have low quality based on their risk of bias assessments (http://onlinelibrary.wiley.com/doi/10.1002/hep.28438/suppinfo).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In similar studies on patients with HBsAg loss, relapse did not occur during the follow-up period, irrespective of whether the patient was HBeAg positive or HBeAg negative [8][9][10][11][12]. In similar studies on patients with HBsAg loss, relapse did not occur during the follow-up period, irrespective of whether the patient was HBeAg positive or HBeAg negative [8][9][10][11][12].…”
Section: Discussionmentioning
confidence: 87%